Some policies to promote research and development activities of businesses - Tuyen, Hoang Van; Minh Nga, Nguyen Thi (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Research and development (R&D) is considered as a tool bringing benefits for businesses in many aspects such as enabling them to introduce quality products/services into markets, enhance their in-house technological capacity,... Many policies of countries, both developed and developing, have been issued with a view to supporting for business R&D. These policies are often delivered, whether in the form of direct or indirect support, via various fiscal instruments. This article clarifies the nature of the policy formation and some state specific policies in relation to support for business R&D. Code: 15090102